2023
DOI: 10.1101/2023.03.20.533342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using accelerometers to infer behaviour of cryptic species in the wild

Abstract: Accelerometery is revolutionising the field of behavioural ecology through its capacity to detect the fine-scale movements of animals resulting from their behaviour. Because it is often difficult to infer the behaviour of wildlife on a continuous basis, particularly for cryptic species, accelerometers potentially provide powerful tools for remote monitoring of their behavioural responses to the environment. The goal of this study was to provide a detailed, calibrated methodology, including practical guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 103 publications
0
1
0
Order By: Relevance
“…In support of this, from calibrated behavioural prediction based on accelerometer sensor data, we recently showed that roe deer spend a minimum of 46-60% of their active time foraging (either feeding and searching for food) depending on the time of day [55]. To index the intensity of foraging, we assessed variation in activity level across the 60-day window at both daily and hourly (circadian) scales.…”
Section: (I) Indexing Foraging Intensity From Metrics Of Activity Levelmentioning
confidence: 92%
“…In support of this, from calibrated behavioural prediction based on accelerometer sensor data, we recently showed that roe deer spend a minimum of 46-60% of their active time foraging (either feeding and searching for food) depending on the time of day [55]. To index the intensity of foraging, we assessed variation in activity level across the 60-day window at both daily and hourly (circadian) scales.…”
Section: (I) Indexing Foraging Intensity From Metrics Of Activity Levelmentioning
confidence: 92%
“…As we wished to compare diurnal versus nocturnal habitat use, we only considered locations recorded at 12:00 (day) and at 00:00 (night). This also ensured that we focused mainly on foraging and/or resting behaviour as roe deer are known to concentrate their inter-patch movements during crepuscular phases (Benoit et al, 2023). All GPS collars integrated an activity sensor which indexed intensity of movement on the x (forwardbackward) and y (sideways) axes (details in Appendix S1.2).…”
Section: Roe Deer Biologging Datamentioning
confidence: 99%